Philosophy in Colonial India - Deshpande, Sharad (Springer, 2015)
This volume focuses on the gradual emergence of modern Indian philosophy through the cross-cultural encounter between indigenous Indian and Western traditions of philosophy, during the colonial period in India, specifically in the 19th and early 20th centuries. This volume acknowledges that what we take ‘Indian philosophy’ or ‘modern Indian philosophy’ to mean today is the sub-text of a much wider, complex and varied Indian reception of the West during the colonial period. Consisting of –twelve chapters and a thematic introduction, the volume addresses the role of academic philosophy in the cultural and social ferment of the colonial period in India and its impact on the development of cross-cultural philosophy, the emergence of a cosmopolitan consciousness in colonial India; as also the philosophical contribution of India to cultural globalization.